Vitamin D Attenuates Ischemia/Reperfusion-Induced Cardiac Injury by Reducing Mitochondrial Fission and Mitophagy - Lee, Tzu-Lin; Lee, Ming-Hsueh; Chen, Yu-Chen; Lee, Yi-Chieh; Lai, Tsai-Chun; Lin, Hugo You-Hsien; Hsu, Lee-Fen; Sung, Hsin-Ching; Lee, Chiang-Wen; Chen, Yuh-Lien (Frontiers in Pharmacology, 2020)
Myocardial infarction is the leading cause of morbidity and mortality worldwide. Although myocardial reperfusion after ischemia (I/R) is an effective method to save ischemic myocardium, it can cause adverse reactions, including increased oxidative stress and cardiomyocyte apoptosis. Mitochondrial fission and mitophagy are essential factors for mitochondrial quality control, but whether they play key roles in cardiac I/R injury remains unknown. New pharmacological or molecular interventions to alleviate reperfusion injury are currently considered desirable therapies. Vitamin D3 (Vit D3) regulates cardiovascular function, but its physiological role in I/R-exposed hearts, especially its effects on mitochondrial homeostasis, remains unclear. An in vitro hypoxia/reoxygenation (H/R) model was established in H9c2 cells to simulate myocardial I/R injury. H/R treatment significantly reduced H9c2 cell viability, increased apoptosis, and activated caspase 3. In addition, H/R treatment increased mitochondrial fission, as manifested by increased expression of phosphorylated dynein-related protein 1 (p-Drp1) and mitochondrial fission factor (Mff) as well as increased mitochondrial translocation of Drp1. Treatment with the mitochondrial reactive oxygen species scavenger MitoTEMPO increased cell viability and decreased mitochondrial fission. H/R conditions elicited excessive mitophagy, as indicated by increased expression of BCL2-interacting protein 3 (BNIP3) and light chain (LC3BII/I) and increased formation of autolysosomes. In contrast, Vit D3 reversed these effects. In a mouse model of I/R, apoptosis, mitochondrial fission, and mitophagy were induced. Vit D3 treatment mitigated apoptosis, mitochondrial fission, mitophagy, and myocardial ultrastructural abnormalities. The results indicate that Vit D3 exerts cardioprotective effects against I/R cardiac injury by protecting mitochondrial structural and functional integrity and reducing mitophagy.